KEPASTIAN HUKUM ATAS BUKTI ROYA YANG HILANG - Gella, Jusuf Kenny Nathanael (The Juris, 2024)
This research aims to find out how to resolve lost evidence. Roya Mortgage itself is an administrative requirement and does not have any significant influence on the law. The formulation of the problem in this research is how to resolve the missing evidence that requires determination based on philosophical, juridical and sociological aspects? The research method used is normative legal research combined with a statutory approach and a conceptual approach. The research results show that a court decision is the only way to resolve the matter as regulated in the Mortgage Law, article 22 paragraph 5, as well as the judge's intervention in determining the application in order to obtain legal certainty.